2017
DOI: 10.1136/esmoopen-2017-000255
|View full text |Cite
|
Sign up to set email alerts
|

Targeting immune checkpoints in breast cancer: an update of early results

Abstract: The immune tumour microenvironment has been shown to play a crucial role in the development and progression of cancer. Expression of gene signatures, reflecting immune activation, and the presence of tumour-infiltrating lymphocytes were associated with favourable outcomes in HER2-positive and triple-negative breast cancer. Recently, immunotherapy with immune checkpoint blockade induced long-lasting responses and improved survival in hard-to-treat malignancies (ie, melanoma and non-small cell lung cancer) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(111 citation statements)
references
References 121 publications
(127 reference statements)
2
109
0
Order By: Relevance
“…Treatment of TNBC remains challenging, because the tumors are highly aggressive and lack therapeutic targets (2, 3). Among the therapeutic options for TNBC, immunotherapy is emerging as a promising approach, but clinical studies in patients with TNBC revealed unsatisfactory outcomes, which is largely attributed to the lack of TILs (36).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of TNBC remains challenging, because the tumors are highly aggressive and lack therapeutic targets (2, 3). Among the therapeutic options for TNBC, immunotherapy is emerging as a promising approach, but clinical studies in patients with TNBC revealed unsatisfactory outcomes, which is largely attributed to the lack of TILs (36).…”
Section: Discussionmentioning
confidence: 99%
“…Reports show that, not only immune infiltrating cells, but also circulating cells can possess an immune suppressive phenotype in cancer patients. [14][15][16] We investigated a set of immune checkpoints/ ligands including PD-1, CTLA-4, TIM-3, LAG-3, TIGIT, VISTA and PD-L1 in peripheral blood mononuclear cells (PBMCs) from healthy donors (n = 32), breast cancer patients (n = 31) and colorectal cancer patients (n = 23). Results showed that the expressions of TIM-3, TIGIT and PD-L1 in PBMCs of PBC patients were significantly higher and LAG-3 was significantly lower compared with HD ( Figure 1(c-f)).…”
Section: Upregulation Of Immune Checkpoints In Circulation Of Breast mentioning
confidence: 99%
“…There is evidence that the low immunogenicity and the intense immunosuppressive tumor microenvironment (TME) of breast cancers (BC) limit the benefit of immunotherapies targeting the adaptive immune system, such as checkpoint inhibitors (CPI) [1,2]. Immunosuppressive mechanisms are essential for the development of normal mammary glands; these strategies are also used by BC cells to promote tumor tolerance and escape from immune surveillance in the early stages of disease, suggesting an important role of adaptive and innate immunity in BC development and progression.…”
Section: Introductionmentioning
confidence: 99%